Counter-heroics Afterword. - Turner, Graeme (Continuum: Journal of Media & Cultural Studies, 2006)
Information about several papers discussed at a conference on cross cultural studies in Australia is presented. The topics are focused on cultural practice and modes of criticisms. The presenters include Melissa Gregg, Jean Burgess and Kris Cohen. The studies presented include blogging, computer hacking and online journalism.